2022
DOI: 10.3390/ijerph19116436
|View full text |Cite
|
Sign up to set email alerts
|

Disparities and Factors Associated with Coronavirus Disease-2019-Related Public Stigma: A Cross-Sectional Study in Thailand

Abstract: Coronavirus disease 2019 (COVID-19)-related public stigma is a major challenge, with scarce available evidence. This study aimed to determine the disparities and factors associated with COVID-19-related public stigma in the Thai population. We conducted a cross-sectional study involving a voluntary online survey in Thailand from 21 April 2020 to 4 May 2020. We invited 4004 participants to complete a series of questionnaires, including the validated COVID-19 public stigma scale and questions on relevant COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The main independent variables were psychological resilience and mental health outcomes of interest, including symptoms of depression, anxiety, perceived stress, and well-being, during the COVID-19 pandemic in Thailand. The Thai versions of the validated measurement tools were used to evaluate mental health and psychosocial outcomes in this study ( Table 1 ) [ 10 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main independent variables were psychological resilience and mental health outcomes of interest, including symptoms of depression, anxiety, perceived stress, and well-being, during the COVID-19 pandemic in Thailand. The Thai versions of the validated measurement tools were used to evaluate mental health and psychosocial outcomes in this study ( Table 1 ) [ 10 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…A numerical rating scale of 0–10 points was used to measure the degree of perceived risk of COVID-19 infection. The degree of perceived risk was classified as none/minimal (0–3 points), moderate (4–6 points), and severe (7–10 points) [ 13 , 21 ].…”
Section: Tablementioning
confidence: 99%
“…Wahyuhadi et al found that 83.55% of the survivors experienced moderate-to-high stigmatization, whereas, only 19.9% reported moderate-to-high levels of stigma in this study, Third, the comparison was made to studies within Thailand. Since no other study has focused on recovered patients, we compared our results with a study conducted by Ruengorn et al [14] which stated that the prevalence of moderate-to-high COVID-19 related public stigma was 75.8%. Accordingly, from these three means of comparison, less severity of stigmatization was observed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Thailand, a mixture of response is observed. Some population reported high stigma, whereas some reported slightly to none [14].…”
Section: Introductionmentioning
confidence: 96%
“…However, according to the DIF analyses, females and individuals with self-reported irreligion had a slightly higher ability to overcome substantial stressors; “item-4, I actively look for ways to replace the losses I encounter in life” compared with males/others and the person's self-identification as religion (Buddhist/Christian/Muslim/Others), respectively. Recently, evidence revealed disparities in COVID-19-related public stigma, especially among males and Buddhists in Thailand 43 . In this circumstance, we hypothesized that some hidden residual traits and characteristics may mediate and contribute to the ability and capacity to coping the negative consequence in both general situations and during the pandemic.…”
Section: Discussionmentioning
confidence: 99%